Making Teacher-Student Interaction Humorous Through Xiangsheng Techniques in the Chinese EFL Classroom - Jiang, Hongji; Mei Leong, Lai (International Journal of English Language Education, 2021)
This paper aims to propose the use of Xiangsheng techniques in the Chinese EFL classroom. Many previous studies have discussed the perceptions and benefits of the use of humor in the language classroom, but there are rarely any discussions on how to initiate humor. This article summarizes 10 Xiangsheng techniques, which meant to engage teachers and students in interactions which are both interesting and humorous. It is hoped that these Xiangsheng techniques will be able to provide insights into the use of humor for those teachers who wish to use it in their language classrooms.